Construction and evaluation of a finger motor feedback system to improve finger dexterity - Takahashi, Shingo; Sakurai, Noriko; Kuroiwa, Yuki; Takahashi, Daishi; Kodama, Naoki (Frontiers in Neuroergonomics, 2025)
IntroductionRecently, a link has been established between cognitive function and hand dexterity in older adults. Declines in cognitive function have been shown to impair performance in finger tapping movements. Research suggest that hand training can improve dexterity, executive function, and cognitive function over time. This underscores the need for effective methods to improve hand and finger dexterity.MethodIn this study, we introduced a new hand training system that provides real-time feedback on finger movements during tapping tasks. We examined the system's impact on the finger dexterity of 32 healthy young participants by using a magnetic sensor finger tapping device (UB-2). During the finger tapping task, the participants performed opening and closing movements either in-phase or anti-phase on both left and right hands for 15 s. They were instructed to tap as quickly as possible. The number of taps, left–right balance, and other relevant data were measured using the UB-2 device.ResultsIn terms of the number of tapping, a significant difference was found between 64.4 without feedback and 68.1 with feedback for the simultaneous opening and closing movements in the dominant hand. In the alternating open-close movement, the significant difference was 50.3 without feedback and 53.4 with feedback. The results showed that the system significantly improved the number and frequency of taps for both hands.ConclusionThe improved tapping performance with feedback suggests that this system can improve hand dexterity.